2018
DOI: 10.1007/s10973-018-7495-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructuring of 1-butyl-4-methylpyridinium chloride in ionic liquid–iron oxide nanofluids

Abstract: Understanding the behavior of ionic liquids (ILs) in ionic liquid-based nanofluids has great significance for its proper application. The phase changes and solidification observed in most ILs offer a great challenge to nanoparticles stabilization. Herein, we have synthesized and characterized a new type of IL-based iron oxide nanofluids using 1-butyl-4-methylpyridinium chloride. We have investigated the formation of dendrite-like nanostructures by 1-butyl-4-methylpyridinium chloride at the IL-nanoparticle inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The viscosity of ILs-based nanofluids is commonly measured by using an Anton Paar Rheometer Physica MCR 301 [37], Brookfield-DVII+Pro [42], HAAKE MARS 2 rheometer (Thermo Fisher Scientific, Karlsruhe, Germany) [43], AR-G2 rotational rheometer from TA instruments (New Castle, Delaware, USA) [44], Viscotester iQ, Haake, Germany [45], capillary viscometer [47], cone and plate type rotary viscometer [49,53,54,62], viscometer (DVI, Brookfield, Middleboro, MA, USA) [50,52], HAAKE RS6000 (Germany) Rheometer [58], and controlled stress rheometer (Haake model RS1) [60]. It is worth noting that most of the viscosity measuring units have a cone and plate type arrangement.…”
Section: Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The viscosity of ILs-based nanofluids is commonly measured by using an Anton Paar Rheometer Physica MCR 301 [37], Brookfield-DVII+Pro [42], HAAKE MARS 2 rheometer (Thermo Fisher Scientific, Karlsruhe, Germany) [43], AR-G2 rotational rheometer from TA instruments (New Castle, Delaware, USA) [44], Viscotester iQ, Haake, Germany [45], capillary viscometer [47], cone and plate type rotary viscometer [49,53,54,62], viscometer (DVI, Brookfield, Middleboro, MA, USA) [50,52], HAAKE RS6000 (Germany) Rheometer [58], and controlled stress rheometer (Haake model RS1) [60]. It is worth noting that most of the viscosity measuring units have a cone and plate type arrangement.…”
Section: Equationsmentioning
confidence: 99%
“…Franca et al [38] studied the thermal conductivity of The concept of nanofluids is used to enhance the thermophysical properties of ionic liquids (ILs) by dispersing a small volume/weight percentage of nanoparticles into base ILs and formed ILs-based nanofluids. Therefore, ILs-based nanofluids have gained interest as HTFs [36][37][38][39][40][41][42][43][44][45]. Several research groups are working on ILs-based nanofluids, and to date, several attempts have been made to quantify their thermophysical properties, such as thermal stability, rheological behavior, thermal conductivity, heat capacity, and thermal performance under natural and forced convection conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viscosity influence of IL nanofluids with particle loadings have been explained by various investigators. Joseph et al [47] observed shear thinning behavior of 1-butyl-4-methylpyridinium chloride/Fe 3 O 4 ionic nanofluids compared to the base fluid. Pamies et al [48] have described the behavior of nanofluids based on 1-ethyl-3-meth-…”
Section: Introductionmentioning
confidence: 99%